PROTON-STIMULATED REDISTRIBUTION OF FE ATOMS IN QUARTZ: EXPERIMENTAL MODELING OF THE SPACE RADIATION EFFECT - Shilobreeva S.N.; Kashkarov L.L.; Barabanenkov M.Yu.; Pustovit A.N.; Zinenko V.I.; Agafonov Yu.A. (My University, 2006)
Space objects (interstellar and interplanetary dust; surfaces of asteroids, meteorites, and the Moon; and others) are affected by various kinds of radiation, e.g., flows of accelerated protons, ions of helium and heavier elements, and others. The radiation impact may induce structural and chemical modifications of the surface of objects (“space weathering”), in particular, the alteration of their optic reflectance. Modification of olivine, enstatite, and diopside crystals under radiation effects that simulate certain types of space radiation was studied.